Development of multiplex serological assay for the detection of human African trypanosomiasis - Nzou, Samson Muuo; Fujii, Yoshito; Miura, Masashi; Mwau, Matilu; Mwangi, Anne Wanjiru; Itoh, Makoto; Salam, Md. Abdus; Hamano, Shinjiro; Hirayama, Kenji; Kaneko, Satoshi (2016)
Human African trypanosomiasis (HAT) is a disease caused by Kinetoplastid infection. Serological tests are useful for epidemiological surveillance. The aim of this study was to develop a multiplex serological assay for HAT to assess the diagnostic value of selected HAT antigens for sero-epidemiological surveillance. We cloned loci encoding eight antigens from Trypanosoma brucei gambiense, expressed the genes in bacterial systems, and purified the resulting proteins. Antigens were subjected to Luminex multiplex assays using sera from HAT and VL patients to assess the antigens' immunodiagnostic potential. Among T. b. gambiense antigens, the 64-kDa and 65-kDa invariant surface glycoproteins (ISGs) and flagellar calcium binding protein (FCaBP) had high sensitivity for sera from T. b. gambiense patients, yielding AUC values of 0.871, 0.737 and 0.858 respectively in receiver operating characteristics (ROC) analysis. The ISG64, ISG65, and FCaBP antigens were partially cross reactive to sera from Trypanosoma brucei rhodesiense patients. The GM6 antigen was cross-reactive to sera from T. b. rhodesiense patients as well as to sera from VL patients. Furthermore, heterogeneous antibody responses to each individual HAT antigen were observed. Testing for multiple HAT antigens in the same panel allowed specific and sensitive detection. Our results demonstrate the utility of applying multiplex assays for development and evaluation of HAT antigens for use in sero-epidemiological surveillance.